2021
DOI: 10.1177/23743735211065265
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perceptions of Healthcare Quality at Hospitals Measured by the Revised Humane Caring Scale

Abstract: The patients’ perceptions are central to quality improvement of the healthcare system worldwide. This study aimed to examine patients’ perceptions of quality care and investigate the demographic factors related to the overall patients’ perceptions. The Revised Humane Caring Scale was distributed to 367 adult patients who were admitted at medical, surgical, and obstetrics and gynecology departments in 2 tertiary hospitals in Oman. Overall patients’ perceptions of quality of care were high, with professionalism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
0
7
0
3
Order By: Relevance
“…Patients’ perceptions of healthcare utilization are significantly related to empathy, trust and perceived daily discrimination ( Torain et al, 2021 ), additionally patients’ insights are key to improving the utilisation of the healthcare system worldwide and can provide relevant and comprehensive information ( Al-Jabri, Turunen & Kvist, 2021 ). At the time of the great challenge of the COVID-19 pandemic, the authors wanted to investigate the importance of the correlation between religion, spirituality and the perception of healthcare service utilisation due to the fact that the majority of the Polish population is of religious/spiritual people, and so it seemed likely that such people could significantly better evaluate the healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…Patients’ perceptions of healthcare utilization are significantly related to empathy, trust and perceived daily discrimination ( Torain et al, 2021 ), additionally patients’ insights are key to improving the utilisation of the healthcare system worldwide and can provide relevant and comprehensive information ( Al-Jabri, Turunen & Kvist, 2021 ). At the time of the great challenge of the COVID-19 pandemic, the authors wanted to investigate the importance of the correlation between religion, spirituality and the perception of healthcare service utilisation due to the fact that the majority of the Polish population is of religious/spiritual people, and so it seemed likely that such people could significantly better evaluate the healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…Mahmoud et al (2019) in Nigerian hospitals found that patients perceived scores on healthcare service quality is lower than their expectations. In their research in Oman hospitals, Al-Jabri et al (2021) found that patients had positive perceptions of high-quality medical care. Patients had varying opinions on healthcare quality with varying healthcare settings and the likely cause of these mixed findings can be attributed to the fact that while several hospitals in the healthcare sector offer the same services, but not all of them are of the same quality (Youssef et al, 1995).…”
Section: Patients' Perspectives On Quality Of Carementioning
confidence: 99%
“…Researchers are paying more attention to the issues with healthcare quality and several studies have been conducted to understand the patients' perspectives during the assessment of the quality of healthcare (Debata et al, 2015). Patients are one of the key stakeholders in high-quality value-based healthcare (Merath et al, 2021) and the patient perspectives can offer significant insights on how attentive and responsive the healthcare system is to their needs (Al-Jabri et al, 2021).…”
Section: Patients' Perspectives On Quality Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…This data, along with guiding principles based on behavioral and cognitive science could facilitate the development of effective risk communication strategies for healthcare providers managing patients’ overusing SABAs and for shifting perceptions about the risks related to SABA overuse in asthma patients. Additionally, the perceptions, attitudes, and behavior of the patients toward the use of SABA may offer crucial and comprehensive details concerning the standard of asthma care management [ 24 ].…”
Section: Introductionmentioning
confidence: 99%